Penerapan model decision making untuk meningkatkan sikap sosial kerjasama pada pembelajaran ips peserta didik kelas iv sekolah dasar - Putri, Florentina Diana; Sadiman, Sadiman; Chumdari, Chumdari (Didaktika Dwija Indria, 2019)
The purpose of this research is to improve the cooperation social attitude in social studies learning throught the used of Decision Making in IV grade of state primary school Munggung 1 Surakarta at 2018/2019 academic year. Subject of the reseach are teacher and student totally 20 students. The research is a classroom action research (CAR) was conducted in three cycles. The data collection techniques used of interview, observation, questionnaire, and documentation. The analysis of the data used is the interactive analysis model of Miles-Huberman. The validity of the data using triangulation of data sources and triangulation of data collection techniques. The first cycle resulting in a percentage of 35% in classical, the second  cycle resulting a percentage of 60% and the third cycle resulting in a percentage of 80% in classical terms.